Design and Application Data Collection for integrated evaluation and monitoring. Issue 1 (February 2021) - Hidayatullah, Muhammad; Wahyudi, Agus Teguh; Esabella, Shinta; Andriani, Titi; Gunawan, G
Abstract: The process of data collection of tax subjects and objects at the Regional Revenue Agency (BAPENDA) of Sumbawa Regency is still manual, where the subject and tax object data are still managed in the form of records on bookkeeping media and office application office media applications such as Microsoft Excel. The need for an application design as a form of digitizing a manual process in the governance system to improve the effectiveness and efficiency of the agency. The research aims to develop Tax Object Subject Data Collection Applications. The application is built with Web-based programming, using the PHP Programming Language and Sublime Text as Tools Editor and MySQL as a data storage medium. The application built can present data collection features related to tax object subject data such as companies, restaurants, hotels, parking and ground water data and can display reports in the form of data related to tax object and object data collection to facilitate the monitoring process in BAPENDA Sumbawa Regency.